Maximal Inequalities for Fractional Brownian Motion with Variable Drift - Cuong, Tran Manh; Quynh, Trinh Nhu (VNU Journal of Science: Mathematics - Physics; Vol 36 No 3DO - 10.25073/2588-1124/vnumap.4447, 2020)
Let BH be a fractional Brownian motion with H∈ (0, 1) and g be a deterministic function. We study the asymptotic behaviour of the tail probability as for fixed x and as for fixed T. Our results partially generalise those obtained by Prakasa Rao in [1].